Weak and Strong Forms of ω-Continuous Functions - Ahmad Al-Omari; Takashi Noiri; Mohd. Salmi Md. Noorani (International Journal of Mathematics and Mathematical Sciences)
We introduce weak and strong forms of ω-continuous functions, namely, θ-ω-continuous and strongly θ-ω-continuous functions, and investigate their fundamental properties.